BLOOD PRESSURE CONTROL RATES PREVIOUS AND DURING THE COVID-19 PANDEMIC IN BRAZIL. (June 2022) - Lima, Lucas; Vitorino, Priscila; Silva, Suelen; Sousa, Ana; Barroso, Weimar
Abstract : Objective: to compare the previous blood pressure control rates with those assessed during the COVID-19 pandemic. Design and method: two cross-sectional studies (march to November 2019 and march to November 2020). Participated patients from health centers of five Brazilian regions that used the TeleMRPA platform to report tests on people diagnosed with and under control of arterial hypertension, aged between 18 and 100 years, included. Data from patients with duplicate or inaccurate information excluded. Blood pressure control measures < or = 140/90 mmHg considered for casual measurements and/or < or = 130/80 for residential measurements. Results: 38.698 patients evaluated, 54.7% in 2019 and 43.9% from northeastern Brazil. There was an increase in patients not using antihypertensive drugs from 52.5% in 2019 to 61.3% in 2020 (p < 0.001) and BMI from 28.1 (± 4.5) to 28.3 (± 4.5) p = 0.010. We did not identify differences in the comparison of SBP (office and MRPA) between the two periods evaluated. There was an increase in DBP both in the office from 83.8 (±11.8) to 84.5 (±11.9), p < 0.001 as that obtained by the MRPA from 79.25 (±9.58) to 79.57 (±9.68), p = 0.001. The variability of DBP reduced from 5.9 (±2.49) to 5.9 (±2.43), p < 0.001, and the mean Pulse Pressure was 50.7 (±14.4) in 2019 to 50.3 (±14.3) in 2020, p = 0.009. There was no change in the control rates considering the office measure which was from 68.9% to 68.6% and the MRPA from 52.4% to 51.4% from 2019 to 2020. Conclusions: blood pressure control remained stable during the COVID-19 pandemic when compared to the previous year. Assessing and monitoring blood pressure control through telemonitoring using home blood pressure monitoring is a simple, easy-to-access, and effective method.